FACTORS AFFECTING THE PERCEPTION OF THE YOUNG GENERATION IN THE BUSINESS OF THE RICE AGRICULTURAL SECTOR IN THE DISTRICT OF CISAAT SUKABUMI REGENCY: FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI GENERASI MUDA DALAM USAHA SEKTOR PERTANIAN PADI SAWAH DI KECAMATAN CISAAT - Imanudin; Nawangwulan Widyastuti; Dwiwanti Sulistyowati (Jurnal Penyuluhan Pertanian, 2022)
Factors that can support agricultural development are human resources, natural resources and appropriate technology. The purpose of this study is to identify the characteristics of the younger generation, analyze the factors influencing the perception of the younger generation in lowland rice business, and develop strategies to strengthen the perception of the younger generation in farming in the lowland rice agricultural sector to achieve food security. The population was taken based on purposive sampling, obtained a sample of 43 respondents from 107 populations. The research method is descriptive quantitative with data collection used in the form of observation, questionnaires/questionnaires, interviews and literature studies. Analysis of the data usedusing descriptive analysis and multiple linear regression. Characteristics of the younger generation who farm 88% are male, the most age is 21-26 and 33-39 years with a percentage of 30%, the age with the most rice business is 33-39 years with 46%, the most education is high school graduates with the percentage of 65% and as much as 65% doing farming are under 5 years. Extension activities (X2.1) and the influence of parents (X2.2) are factors that affect the perception of the younger generation with a real influence (p<0.05).